2013
DOI: 10.1371/journal.pone.0054048
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 Receptor (IGF1R) Expression and Survival in Operable Squamous-Cell Laryngeal Cancer

Abstract: IntroductionPrognosis of patients with operable laryngeal cancer is highly variable and therefore potent prognostic biomarkers are warranted. The insulin-like growth factor receptor (IGFR) signaling pathway plays a critical role in laryngeal carcinogenesis and progression.Patients and MethodsWe identified all patients with localized TNM stage I–III laryngeal cancer managed with potentially curative surgery between 1985 and 2008. Immunohistochemical (IHC) expression of IGF1R-alpha, IGF1R-beta and IGF2R was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
(50 reference statements)
1
34
0
Order By: Relevance
“…Other studies on cancer have revealed that the lack of correlation between mRNA and protein levels can be attributed to mRNA translational silencing, cleavage, or alternative splicing (Dziadziuszko et al 2010, Mountzios et al 2013. In the IGF1R context, alternative mRNA splicing can lead to distinct protein degradation rates in cancer cells (Mountzios et al 2013) while the frequently expressed isoform (alpha) of IGF1R is not directly associated with global IGF1R gene expression (Pollak 2012). Interestingly, reports have demonstrated the impact of IGF1R protein localization on the biological behavior and prognosis of human breast cancer and in clear renal cancer cells (Aleksic et al 2010, Tamimi et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on cancer have revealed that the lack of correlation between mRNA and protein levels can be attributed to mRNA translational silencing, cleavage, or alternative splicing (Dziadziuszko et al 2010, Mountzios et al 2013. In the IGF1R context, alternative mRNA splicing can lead to distinct protein degradation rates in cancer cells (Mountzios et al 2013) while the frequently expressed isoform (alpha) of IGF1R is not directly associated with global IGF1R gene expression (Pollak 2012). Interestingly, reports have demonstrated the impact of IGF1R protein localization on the biological behavior and prognosis of human breast cancer and in clear renal cancer cells (Aleksic et al 2010, Tamimi et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The scoring of the staining pattern was based on the percentage of positive tumor cells: 0=0-5%, 1=6-25%, 2=26-50%, 3=51-100%). The localization of staining for each protein was also indicated either as cytoplasmic or cytoplasmic/membranous or membranous [14]. …”
Section: Methodsmentioning
confidence: 99%
“…In human cells, loss of IGF2R function has been associated with the development of cancers of the breast, lung, liver and ovary [12,13]. However, IGF2R expression was not associated with the clinical features of squamous-cell laryngeal cancer [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in multidisciplinary treatment strategies for LSCC, including targeted surgical extirpation or larynx-preservation protocols implementing chemotherapy or radiotherapy, a large proportion of patients with localized or advanced disease will eventually relapse and die. Indeed, the overall survival of LSCC has not improved much for years [5,6]. Therefore, identifying novel molecular indicators of its malignant behavior is of great interest and could be helpful for early prevention, diagnosis and treatment of LSCC.…”
mentioning
confidence: 99%